PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP FINANCIAL DISTRESS (STUDI PADA PERUSAHAAN PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2014-2019) - Natalia, Ade Rahayu; Sujono, Sujono; Saleh, Salma (-)
This study aims to examine the effect of Non-CEO Duality, Board Size, Non Performing Loan (NPL), Loan To Deposit Ratio (LDR), Return On Assets (ROA), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR). ) to financial distress in banking companies listed on the Indonesia Stock Exchange in 2014-2019. The independent variable in this study is Corporate governance which consists of this Non-CEO Duality, Board Size. Meanwhile, the company's characteristics consist of NPL, LDR, ROA, NIM, and CAR. The financial distress as the dependent variable. The population of this study is the Banking Companies Listed on the Indonesia Stock Exchange 2014-2019. With a total sample of 26 banks or 156 observations determined by the purposive sampling method. The analysis technique used is multiple linear regression analysis and processed using SPSS 25. The results show that Non-CEO Duality has a negative and significant effect on financial distress, Board Size has a significant positive effect on financial distress, NPL has a significant negative effect on financial distress, LDR has a significant positive effect on financial distress. negative and not significant to financial distress, ROA has a positive and not significant effect on financial distress, NIM has a positive and significant effect on financial distress, CAR has a positive and significant effect on financial distress.